PENGARUH MODAL SOSIAL TERHADAP PELAKSANAAN PROGRAM FMA (FARMER MANAGED EXTENTION ACTIVITIES) DI KECAMATAN BAMBANGLIPURO KABUPATEN BANTUL - , FARIDA NURUL H; , Subejo SP., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This reserach aims to: (a) studied the social capital condition in Bambanglipuro Sub-District Bantul Regency, (b) determine the effect of social capital on the implementation of FMA (Farmers Managed Extention Activities) program in Bambanglipuro Sub-District, Bantul Regency, and (c) determine the factors that affect social capital in implementation of FMA (Farmers Managed Extention Activities) programs. Basic method in this research was descriptive analytic method. Sampling of three villages was conducted with a purposive method, which are the villages that implementing FMA programs. From each village was taken 15 farmers randomly. Data were analyzed by proportions test, simple linear regression and multiple linear regression. Research result showed that level of social capital which was owned by farmers at Bambanglipuro Sub-District was categorized strong. Social capital which was owned by farmers significantly influenced in implementing of FMA programs at Bambanglipuro. Variety of factors that influenced the implementation of FMA programs at Bambanglipuro were education of farmers and farmers' attitudes.